2023
DOI: 10.3390/heritage6010026
|View full text |Cite
|
Sign up to set email alerts
|

The Susceptibility to Salt Fog Degradation of Stone Cladding Materials: A Laboratory Case Study on Two Limestones from Portugal

Abstract: The evaluation of stone cladding material suitability can be a challenge due to the way that stone physical and mechanical properties, and characteristics such as mineralogy, might influence stone performance as a cladding element in a ventilated facade application. Salts can affect natural stone performance, and one of the experimental methods available to study and predict it is through accelerated aging tests such as salt fog chamber cycles. Aging test results should include the analysis of critical stone p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…The variation in flexural strength after salt spray ageing was similar to that found in other studies, where the flexural strength usually decreases by around 10% to 30% [29,30]. The increase in flexural strength that occurred in LT ignimbrite was an unusual behaviour, but it also occurred in these studies, and although the variation was close to 9%, it cannot be concluded that it is a significant increase due to the scatter of the results.…”
Section: Flexural Strengthsupporting
confidence: 87%
See 1 more Smart Citation
“…The variation in flexural strength after salt spray ageing was similar to that found in other studies, where the flexural strength usually decreases by around 10% to 30% [29,30]. The increase in flexural strength that occurred in LT ignimbrite was an unusual behaviour, but it also occurred in these studies, and although the variation was close to 9%, it cannot be concluded that it is a significant increase due to the scatter of the results.…”
Section: Flexural Strengthsupporting
confidence: 87%
“…Based on the consulted literature, limestone is one of the most studied building stones in terms of deterioration caused by salt mist. Pires et al [28,29] studied two limestones from Portugal and concluded that after exposure to 45 cycles of salt spray, the samples suffered a loss of mass (between 4.0 and 9.0%) as well as a reduction in modulus of elasticity (between 20 and 30%) and in flexural strength (close to 30%). The behaviour of a group of six limestones, also from Portugal, was studied Carvalho et al [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Fort et al (2014) reported no change in the porosity of Colmenar limestone after 120 salt mist cycles. Similarly, Pires et al (2014) observed an increase in the average pore diameter from 0.14 μm to 0.17 μm after 45 salt mist cycles in biomicrite limestone. These findings provide insights into the response of porosity and pore size distribution in tuff stone materials subjected to salt mist conditions.…”
Section: The Effect Of Salt Mist On Uniaxial Compression Strength (Uc...mentioning
confidence: 63%
“…The application of hydrophobic treatments is a preventive maintenance practice to face the damaging effects of salt and ensure the longevity of construction materials. These coatings serve the following two important purposes, especially when stones are installed as cladding: first, to prevent the intrusion of aqueous solutions and their associated damage [11]; second, to safeguard metal fixings from corrosion in aggressive environments, thereby preventing instability and the potential collapse of slabs [12][13][14]. The application of hydrophobic treatments is a preventive maintenance practice to face the damaging effects of salt and ensure the longevity of construction materials.…”
Section: Introductionmentioning
confidence: 99%